Leadership qualities of university librarians in Malaysia / Kamariah Nor Mohd Desa - Mohd Desa, Kamariah Nor (Institute of Graduate Studies, UiTM, 2015)
The purpose of this study is to explore the leadership qualities required for Malaysian public university librarians that enhances customer satisfaction. The objectives of the study are (1) to examine the perceptions of librarians on their leadership qualities, (2) to examine the perceptions of subordinates on the leadership qualities of their librarians, (3) to examine the perceptions of the heads of departments on the leadership qualities of librarians who are their subordinates, (4) to assess the satisfaction of customers on library services, (5) to examine the relationship between the various dimensions of leadership qualities, (6) to compare the perceptions of different groups of respondents on leadership qualities, (7) to compare the perceptions of users on the importance and performance of library services, and (8) to identify factors (e.g. transformational leadership, emotional intelligence and servant leadership) affecting leadership skills. The study covers 20 public university libraries in Malaysia. Respondents are librarians at all levels, head of departments, subordinates and library customers. The survey method is adopted. Data are collected through four (4) sets of questionnaires. The study adopts the 360 degree method in which the perceptions of respondents are gauged from multiple perspectives, thereby providing more data and information…